Cloning and expression of streptomycin inactivating enzymes APH(6)-Ia and APH(6)-Id - Collins, A.C.; Ashenafi, M.; Saunders, A.A.; Byrnes, W.M. (Cellular and Molecular Biology, 2007)
Discovered in the 1940s by Selman Waksman, the aminoglycoside antibiotic streptomycin is clinically important in the treatment of tuberculosis worldwide. However, strains of Mycobacterium tuberculosis and other pathogenic bacteria have become resistant to streptomycin. One mechanism by which this can occur is through the action of phosphotransferases that attach a phosphate group to position 6 of the streptidine ring of streptomycin, thereby inactivating it. Two such phosphotransferases are APH(6)-Ia from producer strain Streptomyces griseus, and APH(6)-Id found in animal, plant and human pathogenic isolates. Here, we report the subcloning and expression in Escherichia coli of soluble recombinant APH(6)-Ia and Id enzymes. Sequencing of aph(6)-Ia revealed a one-nucleotide disagreement with the published sequence, such that the amino acid at position 262 is an alanine instead of a serine. The sequence of aph(6)-Id is identical to that of the gene found in transposon Tn5393 of plant pathogen Erwinia amylovora. The successful expression of soluble forms of these enzymes now paves the way for experiments to study their structure and function by using site-directed mutagenesis.